Data-Driven, Information-Enabled Regulatory Delivery (OECD Publishing, 2021)
Industries and businesses are becoming increasingly digital, and the COVID-19 pandemic has further accelerated this trend. Regulators around the world are also experimenting with data-driven tools to apply and enforce rules in a more agile and targeted way. This report maps out several efforts undertaken jointly by the OECD and Italian regulators to develop and use artificial intelligence and machine learning tools in regulatory inspections and enforcement. It provides unique insights into the background processes and structures required for digital tools to perform predictive modelling, risk analysis and classification. It also highlights the challenges such tools bring, both in specific regulatory areas and to the broader goals of regulatory systems